Results from the first three rounds of the Scottish demonstration pilot of FOBT screening for colorectal cancer. Issue 4 (26th November 2008) - Steele, R J C; McClements, P L; Libby, G; Black, R; Morton, C; Birrell, J; Mowat, N A G; Wilson, J A; Kenicer, M; Carey, F A; Fraser, C G
Abstract : Objectives: To assess the effects of the first three rounds of a pilot colorectal screening programme based on guaiac faecal occult blood testing (gFOBT) and their implications for a national population-based programme. Methods: A demonstration pilot programme was conducted in three Scottish NHS Boards. Residents aged between 50 and 69 years registered on the Community Health Index were included in the study. Results: In the first round, the uptake was 55.0%, the positivity rate was 2.07% and the cancer detection rate was 2.1/1000 screened. In the second round, these were 53.0%, 1.90% and 1.2/1000, respectively, and in the third round, 55.3%, 1.16% and 0.7/1000, respectively. In the first round, the positive predictive value of the gFOBT was 12.0% for cancer and 36.5% for adenoma; these fell to 7.0% and 30.3% in the second round and were maintained at 7.5% and 29.1% in the third round. The percentage of screen-detected cancers diagnosed at Dukes' stage A was 49.2% in the first round, 40.1% in the second round and 36.3% in the third round. Conclusions: These results are compatible with those of previous randomised trials done in research settings, demonstrating that population-based colorectal cancer screening is feasible in Scotland and should lead to a comparable reduction in disease-specific mortality.